Sources and Methods of Money Laundering Operations - Guesmia, Mohamed (Journal of Legal Studies and Researches, 2024)
It has been known that money laundering is a phenomenon, and it becomes a crime with the availability of its elements, especially the availability of a previous crime about it, and it has a technical floor, in view of the methods of its commission, because the focus of money laundering operations is banking institutions, so the sources and methods of money laundering are diverse with the diversity of its types of commission.